Electronic band structure and specific features of AA- and AB-stacking of carbon nitride (C₃N₄): DFT calculation - Ali Hussain, Reshak, Prof. Dr. (Royal Society of Chemistry, 2014)
Link to publisher's homepage at http://www.rsc.org/